Pistas para perfurar rasgos: colonialidades, gêneros, sexualidades, processos artísticos e... - Salmin, Aline Pinheiro (2021)
This work is generated from the interrelationship between experiences lived during the research process with regard to artistic, political, aesthetic and existential crossings that pervade my body, together with other artists in the contemporary Brazilian scene. The network is woven by a cut in the studies of genders and sexualities, in the search for clues capable of perforating the normative structures given to what I call here bodies. Traversed by the concepts of prosthetic genres and (de)colonialities from a micropolitical perspective of existence, I move through possible ways of building processes of rupture in the normativities of bodies, based on their existential, political, artistic and subjective materialities, considering their multiplicities. Faced with the constant captures and escapes from the hegemonic structures that constantly traverse us, I bet on the body as a possible materiality in consolidating other modes of existence in the world in which we live.